Why Women Matter: the Story of Microcredit - Lott, Charlotte E (Journal of Law and Commerce, 2009)
Alice Amoateng of Ghana is on her second loan of around 100 to set up and expand a clothing trading business. She borrowed the money from a microfinance institution, Sinapi Aba Trust, because she had no access to credit from the banking system. This microfinance institution was able to lend her money by using a group lending system, in which groups of women are jointly responsible for repayment of the loan. The loans allowed her to make her business more profitable and to spend the extra income on her children’s education and her family’s medical expenses. In addition to the loan, she received training in business and leadership, and she was elected to public office to represent her community.